Growth and yield of wheat (Triticum aestivum) adapted to lowland Lombok Island as an alternative food crop for dryland - A Zubaidi; V F A Budianto; A Wiresyamsi; H Abdurrahman (Brawijaya University, 2014)
Wheat is not currently grown as a commercial crop in Indonesia, however since consumption of wheat is steadily increasing and alternative dry season crops are required for farming system diversification, wheat is important to be adapted. Lombok Island has an opportunity for wheat growing and wheat is an alternative crop in drylands. The aims of this experiment is to adapt and screen wheat varieties including national and introduced Australian varieties in lowland Lombok Island. In future, wheat is expected to be an alternative crop for degraded lands. The experimental method used to evaluate growth and yield of 10 wheat varieties to look at the adaptability on the lowland of 200 m asl (Pringgarata) and on higher land of 400 m asl (Aik Bukak). The results showed that at a lower altitude (Pringgarata), wheat growth is slower than in Aik Bukak, which can be caused by the temperature at 200 m asl has exceeded the tolerance limit for grain growth (supra optimal temperature). Wheat can give good yields on 400 m asl, but the yield is decreased at 200 m asl (average 1.68 t/ha vs 0.82 t/ha). This low yield is mainly due to sterility indicated by the low number of grain/spikelet (<2 grain/spikelet). There is genetic variation of wheat crop responses adapted to the lowlands. Nias, Dewata, Mace and Estoc give good yields (> 2 t/ha ), higher than other varieties.